ANALYZING STUDENT WRITING: A COMPREHENSIVE STUDY OF SOCIOLINGUISTICS, SYNTAX, AND VOCABULARY - Ikrimah; Asi, Natalina (Bajang Institute, 2024)
This study presents a comprehensive analysis of an English analytical exposition text written by Indonesian students on